Les parapluies de Cherbourg - Legrand, Michel 1932-2019 (Arte Vidéo [u.a.], 2008)
Set in the French seaside town of Cherbourg, the all-sung dialogue tells of the relationship between shopgirl Geneviève who discovers that she is pregnant after her garage mechanic boyfriend, Guy, is drafted to fight in the Algerian war. She marries Roland Cassard, but lives with the knowledge that her true love lies elsewhere
Orig.: F/BRD 1963
16/9 compatible 4/3. - Filmlaufzeit 87 Min.
Enth. "Les parapluies de Cherbourg" as seen by the actress Virginie Ledoyen ; Mathieu Demy reads from a book by Jean-Pierre Berthomé ; Auszüge aus "Il était une fois ... "Les parapluies de Cherbourg" ; photo gallery
Keywords: Pregnant women / France / Drama; Man-women relationship / Drama; Motion pictures / France; Film; Man-women relationship -- Drama; Motion pictures -- France; Pregnant women -- France -- Drama; Cherbourg (France) / Drama; Frankreich; Cherbourg (France) -- Drama; Feature films; Musical films; Short films